Carbon Dioxide Capture Potential of Chitosan-Nanocrystalline Cellulose Aerogel Composite Materials: Synthesis, Functionalization, and Characterization - Oghenekohwo, Victor (AUC Knowledge Fountain, 2023)
The carbon dioxide capture technology has been established as an invaluable player in the current global efforts to allay the warming of the planet and climate change. In this connection, the study centers on the valorization of waste organic materials for the application described herein. The sorbents, sourced from a combination of by-products of food processing and agricultural residue waste products, viz. seafood waste and sugarcane bagasse, showed prospects for selective carbon dioxide capture, adsorbing up to 5.78 mg/g of the gas at 273 K and 2.82 mg/g at 298 K, as observed on the Micromeritic ASAP 2020 surface area and porosity analyser. Further, thermogravimetric analysis (TGA) showed the materials to possess a decent level of thermal stability, making them fit for the purpose in an industrial setting. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FT-IR), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and viscometry were used to elucidate the microstructure and physicochemical properties of the materials. Drawing on the sorption performance of the aerogels, the low cost of raw materials, potential for scaling up, this work further validates the adsorbent-based carbon capture technology toward curbing the slowly revealing cataclysmic aftermaths of carbon dioxide emissions.